Arabic Learning in Pesantren: Trends in Digitalization and AI Integration A Systematic Literature Review - Ahmad Wildan Sayyidul Bachr; Agus Yasin; Ahmad Farhan Rif’an Najib; Ilham Wahyudi (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2026)
This study examines the trends and patterns of digital media and artificial intelligence integration in Arabic language learning within pesantren contexts. Using a systematic literature review approach guided by PRISMA procedures, it analyzes 20 selected articles published between 2016 and 2026 from major academic databases. The findings reveal a growing use of digital and AI-based media to enhance learner engagement, motivation, and access to diverse learning resources, particularly in receptive skills such as listening and reading. Theoretically, these practices align with Computer-Assisted Language Learning (CALL) and constructivist learning theory, emphasizing interaction, autonomy, and active knowledge construction. However, several limitations persist, including short-term implementations, limited integration of multiple language skills, and the tendency to use technology as a supplementary rather than pedagogically grounded tool. This study contributes by providing a structured synthesis of current research trends and identifying critical gaps in the use of digital and AI-based media in pesantren settings. The findings highlight the need for more comprehensive, integrative, and longitudinal research to develop pedagogically sound and contextually relevant approaches to Arabic language learning.